2017
DOI: 10.4102/safp.v59i3.4690
|View full text |Cite
|
Sign up to set email alerts
|

Muscle pain

Abstract: Muscle pain, also known as myalgia, is most commonly associated with sprains or strains. It frequently presents as redness at the site of injury, tenderness, swelling and fever. Muscle pain may occur as a result of excitation of the muscle nociceptor due to overuse of the muscle, viral infections or trauma. The most important endogenous substance released in response to the damaged tissues or nociceptor nerve endings in regards with muscle pain is adenosine triphosphate (ATP). Optimal pain management involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To improve painful states, small solid needles are inserted into specific points in the body. 20 An overview of systematic reviews done by Liu et al showed that using acupuncture in isolation or as adjunct therapy provided short-term improvements in function and pain for chronic lower back pain. 21…”
Section: Acupuncturementioning
confidence: 99%
“…To improve painful states, small solid needles are inserted into specific points in the body. 20 An overview of systematic reviews done by Liu et al showed that using acupuncture in isolation or as adjunct therapy provided short-term improvements in function and pain for chronic lower back pain. 21…”
Section: Acupuncturementioning
confidence: 99%